Step-by-step explanation
We are to first find the inverse of the function:
![f(x)=(x+12)/(x-4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/xx3gwi2fxlmc7vqw9qi461h1954mn0ear0.png)
![\mathrm{A\:function\:g\:is\:the\:inverse\:of\:function\:f\:if\:for}\:y=f\left(x\right),\:\:x=g\left(y\right)\:](https://img.qammunity.org/2023/formulas/mathematics/high-school/rr9thd5svl9bb7vzb0ijdqzse1ljsznupj.png)
To do so, we will follow the steps below:
Step 1:
![\begin{gathered} write\text{ the function interms of y} \\ y=(x+12)/(x-4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/pvv7n02m1kydaaf0is1csl5rrgpuhmulrm.png)
Step2: Interchange x with y
![x=(y+12)/(y-4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/35aiu3pqomy28t6hjcs066oq85wyg2f6zi.png)
Step 3: solve for y
![\begin{gathered} xy-4x=y+12 \\ xy-y=12+4x \\ y(x-1)=12+4x \\ y=(12+4x)/(x-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3xsasn5sb4ay1k3ekf583tvnip2ddshslw.png)
Thus, the inverse of the function is
![\begin{gathered} f^(-1)(x)^=(12+4x)/(x-1) \\ \\ for \\ x\\e1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/5jrvc8mql4e9t82pettwtwt5ddxzihosyv.png)
Part 2
![f(f^(-1)(x))=f((12+4x)/(x-1))](https://img.qammunity.org/2023/formulas/mathematics/high-school/anyv2r0w6uxklo8qvsos7xj73i26mu188y.png)
Simplifying further
![\begin{gathered} f((12+4x)/(x-1))=((12+4x)/(x-1)+12)/((12+4x)/(x-1)-4)=x \\ Thus \\ f((12+4x)/(x-1))=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/5bocrevxmcwtgif2myvdt7e0zg4bw7geio.png)
Also
![f^(-1)(f(x))=f^(-1)((x+12)/(x-4))](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7q1oa4i4lujox9k12s78dc57fxf6d9l0d.png)
Simplifying further
![\begin{gathered} f^(-1)((x+12)/(x-4))=(12+4*(x+12)/(x-4))/((x+12)/(x-4)-1)=x \\ \\ Thus \\ f^(-1)((x+12)/(x-4))=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7dfvl3pguz5eran2bbb64zba90iwzdsici.png)